Contribution to the knowledge of larval chaetotaxy of the genus Enochrus Thomson: description of five New World species (Coleoptera: Hydrophilidae) - Archangelsky, Miguel (2023)
The primary and secondary chaetotaxy of the larval head capsule and head appendages of five New World species of Enochrus Thomson are described for the first time. These species belong to three subgenera: Enochrus (Hugoscottia) tremolerasi (Knisch), E. (Lumetus) hamiltoni (Horn), E. (Methydrus) barituensis Fernández, E. (Methydrus) ochraceus (Melsheimer) and E. (Methydrus) pygmaeus (Fabricius). Morphometric characters derived from the head capsule and mouthparts are also included, together with detailed illustrations of all characters. A comparative study of the chaetotaxy of four subgenera of Enochrus yields an important number of characters useful to diagnose the larvae of these subgenera, and could be used in future phylogenetic analyses. Several characters showing variation within a subgenus are discussed; additionally, possible diagnostic characters for Enochrus and the subfamily Enochrinae are discussed. The chaetotaxy of two subgenera, Enochrus Thomson and Hydatotrephis MacLeay, still remains unknown, and should be a priority to complete the larval knowledge of the genus Enochrus.